A Study On Omnichannel Authentication For The Banking Industry With Reference To Digilocker”. - Mrs. Ankita Deshpande (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research paper focuses on the omnichannel platform in the Indian banking sector and its uses to the consumer with reference of DigiLocker. It gives an insight on the current need of having an seamless omnichannel banking platform and how it will simplify the customers work. As digital-first approach becomes a necessity, omnichannel banking will give customers the much-sought digital services. Omnichannel approach helps banks improve customer experience, reduce operational costs, and attract new customers.